2013
DOI: 10.1155/2013/786176
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction and Burnout among Intensive Care Unit Nurses and Physicians

Abstract: Introduction. Nurses and physicians working in the intensive care unit (ICU) may be exposed to considerable job stress. The study aim was to assess the level of and the relationship between (1) job satisfaction, (2) job stress, and (3) burnout symptoms. Methods. A cross-sectional study was performed at ICUs at Oslo University Hospital. 145 of 196 (74%) staff members (16 physicians and 129 nurses) answered the questionnaire. The following tools were used: job satisfaction scale (scores 10–70), modified Cooper's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
111
2
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(136 citation statements)
references
References 30 publications
11
111
2
12
Order By: Relevance
“…This is similar to the findings of a study where no difference was found between gender in relation to burnout. 16 However, other various studies found age, gender, level of education, marital status to be associated with burnout. 3,17,18 Conversely, in this study high level of burnout was found among married participants but there was no significant association between marital status and burnout (P >0.05).…”
Section: Sociodemographic Characteristicsmentioning
confidence: 96%
See 1 more Smart Citation
“…This is similar to the findings of a study where no difference was found between gender in relation to burnout. 16 However, other various studies found age, gender, level of education, marital status to be associated with burnout. 3,17,18 Conversely, in this study high level of burnout was found among married participants but there was no significant association between marital status and burnout (P >0.05).…”
Section: Sociodemographic Characteristicsmentioning
confidence: 96%
“…3 The reason is that the experienced in the career are stable, become skilled and competent and become more familiar with the profession and they know how to deal with stressors faced at work. 16 …”
Section: Work Related Factorsmentioning
confidence: 99%
“…Perceived depersonalization had a moderate inverse association with reduced job satisfaction in a study of 129 ICU nurses (r = -0.313; p < .001) [43] .…”
Section: Depersonalizationmentioning
confidence: 95%
“…Highest scores reflected multicenter studies with a large sample size, clearly defined outcome measures, demonstrated survey instrument validation, high survey response rate, identified complex associations within the results and demonstrated relevance to health services management [41,42] . Conversely, the lowest scoring study was conducted in a single site with a small convenience sample, and implications for practice were not clearly articulated limiting broader generalization of results [43] .…”
Section: Qumentioning
confidence: 99%
See 1 more Smart Citation